Optimal planning of biodiesel supply chain using a linear programming model - Valizadeh, Maryam; Syafiie, Syafiie; Ahamad, Intan Salwani (IEEE (IEEE Xplore), 2014)
This paper pre sents a method for the improvement of economic performance of biofuel supply chain. A mathematical model is proposed for optimal planning of biofuel supply chain in order to minimize the total operational costs. The model is linear and takes into consideration the availability of feedstock and biorefineries and determines the optimal schedule for harvesting and transportation of biomass feedstocks, biodiesel production and distribution over the planning horizon. The model is applied to a case study for the production of biodiesel from palm oil and jatropha in Malaysia.